Using the MPX5500DP Sensor for Monitoring Microcontroller-Based HVAC Systems and IOT - Rizki Aulia Nanda; Agus Supriyanto; Karyadi; Fathan Mubina Dewadi (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2023)
MPX5500DP is a sensor designed to measure how much air pressure is traveling in a channel or piping system. The MPX5500DP sensor has an analog output value that can be converted into a digital signal to display data on how much air pressure is being generated. By utilizing the MPX5500DP sensor the purpose of this study is to measure air pressure in HVAC systems with Micro SD data storage and IOT (Internet Of Things) based Web Browsers. The method used in implementing the MPX5500DP sensor is, selecting materials, making tools, installing sensors and testing. The test results obtained from Micro SD storage are the average air pressure value of 15.76 kPa. The IOT test produced an average air pressure of 15.67 kPa. At the time of testing, there were problems where data transmission was very slow so that for 30 minutes the test only received 14 air pressure data that were read on the Web Browser, namely ThingSpeak. However, the IOT test on an air pressure gauge using the MPX 5500DP sensor was successful. The success of the IOT system in monitoring HVAC air pressure can assist in monitoring the HVAC system in multi-storey buildings.